Implementation of Art and Technology in Batik Purwakarta - Ratnadewi, Ratnadewi; Pandanwangi, Ariesa; Prijono, Agus (JTAM (Jurnal Teori dan Aplikasi Matematika), 2020)
Indonesia is dominated by cities that have a history of batik, but Purwakarta does not have a history of batik. But thanks to the persistence of policy holders, Purwakarta currently has batik obtained by elevating the local wisdom of the city of Purwakarta. After surveys and interviews, several batik motifs were designed. The batik motif shape, size and position will be studied which will formulate mathematical equations based on basic geometric shapes such as circles, arches, lines, rectangles, which are implemented into the form of computer graphics (turtles) graph and explained in the form of an algorithm (pseudocode) computer programming to make autogenerative motifs on Purwakarta batik that did not exist before. Batik design is inspired by food and tourist locations which form the basis of the formation of typical Purwakarta batik motifs. Jatiluhur Dam, Datura Metel L. Flower, Sate Maranggi, Mangosteen Fruit is a local wisdom owned by the city of Purwakarta. The results of the morning glory batik design and Jatiluhur dew through mathematical and turtle charts are then formulated so that the batik motif design can be saved by documenting the mathematical equation or the pseudocode of the batik motif. With the results of digital motifs, the process of repeating patterns, duplicating and storing data becomes easier.